Microbiota assessment of fresh-cut apples packaged in two different films - Madureira, Joana (2019)
The aim of this work was to assess the natural microbiota of packed fresh-cut apples during refrigerated storage. Two different films were tested for the package, a biodegradable (PLA) film and a conventional and commercial one (OPP). Two antioxidant additives were applied, a natural olive pomace extract and the commercial ascorbic acid used by the industries. The results revealed lower bacteria counts in samples with olive pomace extract and PLA films than in those with ascorbic acid and OPP films after 5 and 12 days of storage. These findings suggest that the use of such natural extracts as additives in fruits could delay the growth of mesophilic bacteria. The characterization and identification of the bacterial isolates from fresh-cut apple samples showed that the most prevalent species were Citrobacter freundii, Staphylococcus warneri, Pseudomonas oryzihabitans, Alcalinogenes faecalis, Corynebacterium jeikeium, Micrococcus spp., Pantoea aglomerans and Bacillus spp. Furthermore, an increase in the microbial diversity during the storage time at refrigerated temperatures was observed, except for the sample treated with olive pomace extract and packaged in OPP film. The highest microbial diversity was found for samples with ascorbic acid as an additive. This could indicate a negative effect of ascorbic acid on the microbial inhibition of apple slices. The natural olive pomace extract demonstrated potential as an antimicrobial additive for fresh-cut apples.